2018
DOI: 10.1111/1755-6724.13691
|View full text |Cite
|
Sign up to set email alerts
|

The Cretaceous Turn of Geological Evolution: Key Evidence from East Asia

Abstract: this work focuses on one of the critical points of Earth's history when the Solar System passed through the most distant point of its galactic orbit. During this event, Earth may have suffered from maximum extension, associated with its relative proximity to the Sun at that time, followed by long‐term contraction related to its later distancing. This paper is based on generalized data on the Cretaceous evolution of the Earth as a whole and of East Asia in particular. The evidence suggests that major geological… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
13
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(16 citation statements)
references
References 75 publications
(109 reference statements)
3
13
0
Order By: Relevance
“…The present geochemical and geochronological analyses revealed that In summary, the present study positively suggests a plume-related change of the mantle composition during the Jurassic-early Cretaceous (Nechaev et al, 2018); that is, from a primitive mantle to EM2, with respect to a change in subduction regime, from deep-angle during the Permian-Triassic to shallow-angle during the Triassic to Early Cretaceous, then back to deep-angle again in the mid-Cretaceous to Paleogene. The above conclusions with relevant tectono-magmatic interpretations in southern Primorye appear consistent with the data from the circum-Sea of Japan region, for example, NW China, Korean peninsula, and southwest/northeast Japan (Figure 17); on the contrary, they are significantly inconsistent with the widely accepted tectonic views of large-scale strike-slip tectonics in the early to mid-Cretaceous East Asia (e. g., Khanchuk et al, 1996, Khanchuk et al, 1997, Khanchuk et al, 2019Maruyama et al, 1997;Yamakita & Otoh, 2000;Golozoubov, 2006;Liu et al, 2017;Li et al, 2020).…”
Section: Discussionsupporting
confidence: 68%
See 3 more Smart Citations
“…The present geochemical and geochronological analyses revealed that In summary, the present study positively suggests a plume-related change of the mantle composition during the Jurassic-early Cretaceous (Nechaev et al, 2018); that is, from a primitive mantle to EM2, with respect to a change in subduction regime, from deep-angle during the Permian-Triassic to shallow-angle during the Triassic to Early Cretaceous, then back to deep-angle again in the mid-Cretaceous to Paleogene. The above conclusions with relevant tectono-magmatic interpretations in southern Primorye appear consistent with the data from the circum-Sea of Japan region, for example, NW China, Korean peninsula, and southwest/northeast Japan (Figure 17); on the contrary, they are significantly inconsistent with the widely accepted tectonic views of large-scale strike-slip tectonics in the early to mid-Cretaceous East Asia (e. g., Khanchuk et al, 1996, Khanchuk et al, 1997, Khanchuk et al, 2019Maruyama et al, 1997;Yamakita & Otoh, 2000;Golozoubov, 2006;Liu et al, 2017;Li et al, 2020).…”
Section: Discussionsupporting
confidence: 68%
“…By reporting the analytical results, this article discusses possible origin of dyke-generating magmas, and their secular change from the Permo-Triassic to Cretaceous-Paleogene time. We also compare the present results with those on similar dykes in other parts of southern Far East Russia, China, Korea, and Japan (e.g., Davis, 2003;Guo et al, 2007;Liu et al, 2012;Nechaev et al, 2018;Pouclet et al, 1995;Tsuchiya et al, 2005;Wu et al, 2017) for finding further geotectonic implications to the circum-Sea of Japan region. Previous studies assumed the subduction-related origin of these dykes and related volcanic and plutonic complexes; nonetheless, some emphasized possible links to large-scale strike-slip tectonics, including asthenospheric diapirism over 1000 km during the Cretaceous period (Grebennikov et al, 2016;Khanchuk et al, 2019;Martynov et al, 2016;Simanenko et al, 2002), and/or to a complicated plume influence onto the subduction system (Nechaev et al, 2018).…”
supporting
confidence: 67%
See 2 more Smart Citations
“…Critical elements in coal and coal-bearing sequences, such as Li, Sc, V, Ga, Ge, Se, and Y and rare earth elements (REY, or REE+Y) Zr, Nb, Au, and Ag, and platinum group elements, Re, and U, have attracted great attention in recent years [1][2][3][4][5][6][7][8], as these elements in some coals and coal-bearing sequences may have relatively high concentrations, comparable to those of conventional ore deposits [9,10]. Nowadays, world economies largely depend on high technologies in which critical elements play a vital role because they are driving some of the biggest advancements in technology and energy efficiency in the world [3,11].…”
Section: Introductionmentioning
confidence: 99%